Counter-Narratives
XI, 313 p. 5 illus.
Keywords: Saudi Arabia and Yemen are two countries of crucial importance in the Middle East and yet our knowledge about them is highly limited, while typical ways of looking at the histories of these countries have impeded understanding. Counter-Narratives brings together a group of leading scholars of the Middle East using new theoretical and methodological approaches to cross-examine standard stories, whether as told by Westerners or by Saudis and Yemenis, and these are found wanting. The authors assess how grand historical narratives such as those produced by states and colonial powers are currently challenged by multiple historical actors, a process which generates alternative narratives about identity, the state and society.